Considering the Virtual Classroom: A Call to Middle Level Education Programs - Brooke B Eisenbach (Middle Grades Review, 2016)
Today’s classrooms are changing and moving beyond the walls of a traditional school environment. With each passing year, a growing population of middle level learners are logging into full-time, or blended learning virtual courses. However, teachers often lack the training and experience necessary to address the developmental needs of middle level learners within this new context. In an effort to prepare tomorrow’s educators for the reality of the 21st century classroom, it’s time to consider our post-secondary education programs, and the manner in which we prepare our teacher candidates to teach middle level learners within the virtual platform.
Keywords: Virtual Education; Middle Level Education; Teacher Preparation